KESIAPAN KETAHANAN PANGAN PROPINSI JAMBI DALAM MENGHADAPI MEA 2015 - Rina Astarika (Jurnal Ilmiah Universitas Batanghari Jambi, 2015)
Globalization can’t avoided, and the end 2015 ASEAN Economic Community (AEC) by reaffirming realized based neoliberal economic cooperation. This situation makes the government should be able to improve the competitiveness of domestic producers, so that the necessary policies that protect the lower classes of society and increase the capacity of small-scale economic actors. Jambi province as one of the otononom in Indonesia, the contribution of agriculture play an important role in improving the GDP (Gross Domestic Product) . But the role of the agricultural sector from year to year is also likely to decline, this was due to the increasing role of trade, mining, and manufacturing sector, and the increasing number of agricultural land converted into land not agricultural . This condition will threaten the future of food security in Jambi province. In order for food security in Jambi stronger required careful planning and cross-sectoral support, so it’s able to support the creation of food persistance.Keywords: Globalization, food security, Jambi